2021
DOI: 10.1155/2021/5511866
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Technologies of Natural Language‐Enabled Chatbots: A Review and Trend Forecast Using Intelligent Ontology Extraction and Patent Analytics

Abstract: Natural language processing (NLP) is a critical part of the digital transformation. NLP enables user-friendly interactions between machine and human by making computers understand human languages. Intelligent chatbot is an essential application of NLP to allow understanding of users’ utterance and responding in understandable sentences for specific applications simulating human-to-human conversations and interactions for problem solving or Q&As. This research studies emerging technologies for NLP-enabled i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 60 publications
1
9
0
Order By: Relevance
“…Regarding the NLP topics or sub-domains that are most applied for and researched, this study found that the field of speech recognition is gaining an increasing interest in research and invention activities, which is supported by the findings of Chao et al in [8]. The growing enthusiasm for speech recognition could be attributed to the recent commercial hype about personal assistants, such as Siri, and other conversational AI products.…”
Section: Nlp Abstract Shift Over Timesupporting
confidence: 65%
See 1 more Smart Citation
“…Regarding the NLP topics or sub-domains that are most applied for and researched, this study found that the field of speech recognition is gaining an increasing interest in research and invention activities, which is supported by the findings of Chao et al in [8]. The growing enthusiasm for speech recognition could be attributed to the recent commercial hype about personal assistants, such as Siri, and other conversational AI products.…”
Section: Nlp Abstract Shift Over Timesupporting
confidence: 65%
“…When it comes to NLP patent analysis, Chao et al in [8] provided a comprehensive study of the emerging technologies in the field of NLP with an intense focus on exploring the technological developmental trends of NLP-enabled intelligent chatbots. The study adopted several text-mining techniques, such as document term frequency analysis (TF-IDF) to identify the key terminologies used in NLP patents, clustering methods to analyze the sub-domains of NLP that have a higher application rate in patents, and Latent Dirichlet Allocation for topic modeling to extract the key topics in the patent dataset.…”
Section: Related Workmentioning
confidence: 99%
“…The use of chatbot in combination with Customer Relationship Management -CRM-can improve the ability of the company to offer information towards its clients (Setiawan, et al, 2019). The efficacy of chatbots is a function of the Natural Language Processing -NLP-algorithm adopted for the development (Chao, et al, 2021): Convolutional Neural Networks-CNN-and Long Short-Term Memory-LSTM- (Massaro, et al, 2021) algorithms can be applied to optimize the recognition of words and phrases and a combination of questions and answers. The application of NLP in chatbot systems can also improve the efficacy of health assistance as for telemedicine applications (Omoregbe, et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Customer support chatbots are becoming increasingly commonplace. There is renewed curiosity in chatbots because of NLIs [19], [20]. Customers can type in questions and get clear responses in natural language because of chatbots' human-like dialogue [21].…”
mentioning
confidence: 99%
“…The functionality of AI allows apps to learn from every user and their behavior [38], [39]. Through their mobile app, Tala screens loan applicants with little to no credit history and disburses funds [20], [21], [36]. The program allows the company to evaluate these previously ineligible clients by calculating their default risk based on Meta and S-M-S facts [12], [15]- [19], [22], [25], [39], [40].…”
mentioning
confidence: 99%